Intake of Resistant Starch Reduces Colonic Inflammation in the Colon of Obese, C57BL/6 Mice Fed a High Fat Diet. (14th June 2022) - Zeng, Huawei; Safratowich, Bryan; Liu, Zhenhua; Bukowski, Michael
Abstract: Objectives: Intake of fiber has beneficial effects for gut health which may be due to short chain fatty acid (e.g., butyrate) production during colonic fermentation. In contrast, obesity and obesogenic diets are linked to increased colonic inflammation. We tested the hypothesis that increasing fiber intake reduces colonic inflammation in C57BL/6 mice fed an obesogenic diet. Methods: Four-week-old male C57BL/6 mice were assigned to 5 dietary groups (n = 22/group) for 24 weeks: (1) AIN93G as a control diet (AIN); (2) a high fat diet (HFD, 45% energy fat); (3) HFD + 5% resistant starch from corn (RS); (4) HFD + 10%RS; or (5) HFD + 20%RS. We used biochemical, gas chromatography with flame-ionization detection, and histological approaches to determine the effect of RS on the inflammatory status in the colon of C57BL/6 mice fed HFD. Results: All animals receiving HFD exhibited increases in body mass and body fat composition compared to the AIN group irrespective of RS dosage. However, the HFD + RS groups exhibited an increase in fecal butyrate content in a RS dose-dependent manner over the HFD group with 2.1- and 3.3-fold increase in the HFD + 10%RS and HFD + 20%RS groups, respectively. Consistent with butyrate's beneficial effects, there were concomitant > 0.5-fold decreases in inflammatory cell infiltration and b-catenin protein staining in the colon of animals receiving 20% RS supplementation relative to the HFD group. Conclusions: These data indicate that even under obesogenic conditions in a mouse model, RS consumption reduces colonic inflammation. Funding Sources: This work was supported by U.S. Department of Agriculture, Agricultural Research Service, research project 3062-51, 000-056-00D.